A high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material

By using high-entropy rare earth chromate materials, the oxidation and volatility of Cr elements is suppressed, and the problem of poor aging stability of traditional perovskite structure high-temperature NTC materials at high temperatures is solved, and a negative temperature coefficient in the range of 0℃~1300℃ is achieved. Characteristics and high temperature aging stability.

CN116947466BActive Publication Date: 2025-02-07XINJIANG TECH INST OF PHYSICS & CHEM CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310945487.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-07
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

Traditional perovskite structure high-temperature NTC materials volatilize Cr elements in high temperature environments, resulting in non-density sintering, poor uniformity, and poor high-temperature aging stability, which cannot meet the technical performance requirements for high-temperature applications.

Method used

Using high-entropy rare earth chromate (La0.2Nd0.2Sm0.2Eu0.2Gd0.2)CrO3 material, it is prepared by wet three-dimensional vibration ball milling, drying, powder calcining, cold isostatic molding and high-temperature sintering to inhibit Cr oxidation and volatility of the material improves the high-temperature phase/structural stability.

Benefits of technology

The material exhibits obvious negative temperature coefficient characteristics in the temperature range of 0℃~1300℃, has excellent high-temperature aging stability, and has resistance drift rate of only 4.35%. It is suitable for the manufacture of high-temperature negative temperature coefficient thermistors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116947466B_ABST
    Figure CN116947466B_ABST
Patent Text Reader

Abstract

The present invention relates to a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material, belonging to the field of semiconductor sensors, and aims to solve the existing perovskite structure high-temperature NTC material. Under high temperature environment, the Cr element in the system will volatilize in the form of gaseous CrO3, showing poor high-temperature aging stability. The high-temperature negative temperature coefficient thermistor material uses lanthanum trioxide, neodymium trioxide, samarium trioxide, europium trioxide, gadolinium trioxide and chromium trioxide as raw materials, and undergoes wet three-dimensional vibration ball milling, powder calcination, cold isostatic pressing, and high-temperature sintering to obtain a perovskite structure (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3 thermosensitive material. The electrical performance parameters of this series of materials are: B 0℃ / 1300℃ =2044±1.42%K,ρ 1300℃ =1.45×10 3 ±1.73%Ω·cm. The high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3 has excellent negative temperature coefficient characteristics in the temperature range of 0~1300℃, and shows good high temperature aging stability at high temperatures (the resistance drift rate is only 4.35% after aging for 500 hours at 1300℃).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of semiconductor sensors, in particular to a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3. Furthermore, the present application provides a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material, a preparation method thereof, and its application in the field of semiconductor sensors. The thermistor material has obvious negative temperature coefficient characteristics and stable high-temperature aging characteristics in a wide temperature range of 0°C to 1300°C. Background Art

[0002] Compared with traditional precious metal resistors and thermocouples, negative temperature coefficient (NTC) thermistors are widely considered to be the most economical and extensive choice in the fields of temperature sensing, compensation and surge current suppression due to their advantages such as small size, low cost and short response time. However, with the national industrial adjustment and technological upgrading, the operating temperature of components in many fields such as aerospace, automotive electronics and military science has gradually increased, which has put forward higher requirements for the upper temperature measurement limit of high-temperature negative temperature coefficient (NTC) thermistors. However, traditional NTC materials, such as spinel oxides, have limited aging stability and accuracy under high temperature conditions, which is not conducive to high temperature applications.

[0003] At present, reports on high-temperature NTC materials are mainly focused on chromium-based perovskites and their composite structural materials. For high-temperature NTC materials with perovskite structure, although the applicable temperature range is wide (25℃~900℃) and the electrical properties are adjustable; however, in high-temperature environments, chromium-based perovskites are prone to element volatilization, which often makes it difficult to sinter the material densely in the air and has poor uniformity. In addition, side reactions will occur at the grain boundaries, precipitating the second phase, resulting in resistivity drift, which seriously causes the resistance value of thermistors to disperse and drift continuously, showing poor high-temperature aging stability, which is not conducive to large-scale manufacturing. For the perovskite composite of high-resistance oxide and low-resistance phase, according to the mixing rules of electrical properties, it is expected to obtain high-temperature NTC materials suitable for a wide temperature range and a high upper temperature measurement limit; however, subsequent studies have found that this composite phase, at high temperature, due to the percolation effect and ion migration between the two phases, causes changes in the grain boundary resistance and the carrier concentration in the bulk phase of the composite material, causing the resistivity of the material to drift continuously, and the high-temperature stability is still poor.

[0004] In summary, traditional perovskites and their composite structures can no longer meet the increasingly stringent technical performance requirements for high-temperature NTC materials at this stage. Therefore, it is imperative to develop new high-temperature NTC materials with good high-temperature aging stability and high precision. Summary of the invention

[0005] The purpose of the present invention is to provide a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material for existing high-temperature perovskite-structured NTC materials. Under high-temperature conditions, the Cr element in the system will volatilize in the form of gaseous CrO3, which often leads to the problem that the material is difficult to sinter densely in the air, has poor uniformity, and exhibits poor high-temperature aging stability.

[0006] In recent years, the emerging high-entropy ceramics have attracted the attention of inventors due to their excellent properties brought about by the synergistic effect of multiple elements, such as the antioxidant and corrosion-resistant properties brought about by the kinetic hysteresis effect, which will inhibit the oxidation and volatilization of Cr at high temperatures; the thermodynamic high-entropy effect makes the material have better high-temperature phase / structural stability; the severe lattice distortion in the structure leads to low thermal conductivity and lower material constant B value, providing conditions for a wider application temperature range; therefore, according to the new strategy of multi-component design of high-entropy ceramics, the present application prepares a perovskite structured high-entropy rare earth chromate ceramic material that can be used in the field of wide temperature range (0~1300℃) and high-temperature negative temperature coefficient thermistors.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A high entropy rare earth chromate high temperature negative temperature coefficient thermistor material, the chemical formula of which is (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3;

[0009] The electrical performance parameters of the negative temperature coefficient thermistor material are as follows: 0℃ / 1300℃ = 2044 ±1.42% K, ρ 1300℃ =1.45×10 3 ±1.73% Ω·cm, applicable temperature range is 0℃-1300℃.

[0010] The negative temperature coefficient thermistor material is prepared by mixing and sintering raw materials of lanthanum trioxide, neodymium trioxide, samarium trioxide, europium trioxide, gadolinium trioxide and chromium trioxide according to a chemical formula molar ratio.

[0011] The negative temperature coefficient thermistor material is prepared by a method comprising the following steps:

[0012] a. According to the molar ratio of La:Nd:Sm:Eu:Gd:Cr=1:1:1:1:1:5, weigh oxide powders of lanthanum trioxide, neodymium trioxide, samarium trioxide, europium trioxide, gadolinium trioxide and chromium trioxide respectively and mix them to obtain an initial mixture; after wet three-dimensional vibration ball milling the initial mixture for 8-12 hours, dry the wet-milled slurry at a temperature of 100°C, take it out and place it in an agate mortar for manual grinding for 1-4 hours to obtain a precursor powder;

[0013] b. calcining the precursor powder obtained in step a at 1100° C. for 2 to 6 hours, and then manually grinding for 0.5 to 10 hours to obtain a perovskite phase powder;

[0014] c. The perovskite phase powder obtained in step b is pressed into blocks using a uniaxial hydraulic press to obtain a second formed block; the second formed block is cold isostatically pressed to obtain a third isostatically pressed block; the third isostatically pressed block is sintered at 1550° C. for 5-35 hours to obtain a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material.

[0015] In the step a, oxide powders of lanthanum trioxide, neodymium trioxide, samarium trioxide, europium trioxide, gadolinium trioxide and chromium trioxide are weighed and mixed according to the molar ratio of La:Nd:Sm:Eu:Gd:Cr=1:1:1:1:1:5, placed in a ball mill, agate is used as the ball milling medium, and analytical pure anhydrous ethanol is used as the dispersion medium, and wet three-dimensional vibration ball milling is performed for 8 hours. The wet-milled slurry is dried at a temperature of 100°C, taken out, placed in an agate mortar and manually ground for 2 hours to obtain a precursor powder.

[0016] In step b, the precursor powder obtained in step a is calcined at 1100° C. for 5 hours and then manually ground for 2 hours to obtain a perovskite phase (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3 powder.

[0017] In the step c, the third isostatically pressed block is sintered at 1550° C. for 15 hours to obtain a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material.

[0018] In the step c, the perovskite phase powder obtained in step b is pressed by a uniaxial hydraulic press at 15 kg / cm 2The second molded block was pressed at a pressure of 300 MPa for 2 minutes to obtain a second molded block; the second molded block was cold isostatically pressed and maintained at a pressure of 300 MPa for 3 minutes to obtain a third isostatically pressed block; the third isostatically pressed block was sintered at a temperature of 1550°C for 15 hours to obtain a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3.

[0019] The application of high entropy rare earth chromate high temperature negative temperature coefficient thermistor material in the field of semiconductor sensors. The chemical formula of the high entropy rare earth chromate high temperature negative temperature coefficient thermistor material is (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3.

[0020] As mentioned above, when chromium-based perovskite-type and its composite phase thermistor ceramics are used for a long time in a high-temperature environment, the Cr element in the system will volatilize in the form of gaseous CrO3, resulting in poor high-temperature aging stability and unable to meet the application requirements in higher environments. A high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material is provided.

[0021] The inventors have found that high entropy rare earth chromate (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3 has obvious negative temperature coefficient characteristics in the temperature range of 0~1300℃. This type of high entropy material shows a wide test temperature range, and the maximum temperature limit can reach 1300℃. At the same time, due to the entropy-stabilized structure, it exhibits excellent aging stability. The experimental results show that the material has excellent aging stability at 1300℃, and the resistance drift rate is only 4.35% after aging for 500 hours. It can be used to manufacture high-temperature negative temperature coefficient thermistors with high stability. At the same time, the material has stable electrical properties, high linear correlation, and good consistency, which is suitable for manufacturing thermistor components in high temperature environments.

[0022] In summary, the present application provides a high-entropy rare earth chromate used as a high-temperature negative temperature coefficient thermistor material, a preparation method thereof, and its application in the field of semiconductor sensors. The method adopts a wet three-dimensional vibration ball milling method to mix and ball-mill analytically pure lanthanum trioxide, neodymium trioxide, samarium trioxide, europium trioxide, gadolinium trioxide and chromium trioxide in a stoichiometric ratio, and then dries, calcines the powder, and ball-mills it again. The powder is then cold isostatically pressed, sintered at high temperature, and annealed at high temperature to obtain a thermistor material. The high-entropy rare earth chromate negative temperature coefficient thermistor material (La chromate) prepared by the present invention 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )The electrical performance parameters of CrO3 are as follows: B 0℃ / 1300℃ =2044 ±1.42% K,ρ 1300℃ =1.45×10 3 ±1.73% Ω·cm. The thermosensitive material has an obvious negative temperature coefficient characteristic in the temperature range of 0℃-1300℃, and has good electrical performance consistency; after aging for 500 hours at 1300℃, the resistance drift rate is only 4.35%, and the high-temperature electrical performance is stable and the sensitivity is high.

[0023] In summary, due to the adoption of the above technical solution, the present invention has the following beneficial effects:

[0024] (1) Thermosensitive material of the present invention (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3 has NTC characteristics in the temperature range of 0℃~1300℃, with a wide test temperature range;

[0025] (2) Thermosensitive material of the present invention (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 ) After aging for 500 hours at 1300℃, the resistance drift rate of CrO3 is only 4.35%, showing excellent high temperature aging stability;

[0026] (3) Thermosensitive material of the present invention (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )The high resistivity of CrO3 in high temperature environment ensures the accuracy of its measurement. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will now be described by way of example with reference to the accompanying drawings, in which:

[0028] Figure 1 For the present invention (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )XRD (X-ray diffraction) pattern of CrO3 material.

[0029] Figure 2 For the present invention (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )The relationship between the resistivity and temperature of CrO3 material.

[0030] Figure 3 For the present invention (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )Relationship between resistance drift rate and aging time of CrO3 material at 1300 °C. DETAILED DESCRIPTION

[0031] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.

[0032] Any feature disclosed in this specification, unless otherwise stated, can be replaced by other equivalent or alternative features with similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.

[0033] Example 1

[0034] a. According to the molar ratio of La:Nd:Sm:Eu:Gd:Cr=1:1:1:1:1:5, weigh out the oxide powders of lanthanum trioxide, neodymium trioxide, samarium trioxide, europium trioxide, gadolinium trioxide and chromium trioxide respectively and mix them to obtain an initial mixture; after wet three-dimensional vibration ball milling of the initial mixture for 8 hours, dry the wet-milled slurry at a temperature of 100 °C, take out and place it in an agate mortar and grind it manually for 2 hours to obtain a precursor powder.

[0035] b. The precursor powder obtained in step a was calcined at 1100° C. for 5 hours and then manually ground for 2 hours to obtain a perovskite phase powder.

[0036] c. The perovskite phase powder obtained in step b was pressurized by a uniaxial hydraulic press at 15 kg / cm2 The second molded block was pressed under a pressure of 300 MPa for 2 minutes to obtain a second molded block; the second molded block was cold isostatically pressed and maintained at a pressure of 300 MPa for 3 minutes to obtain a third isostatically pressed block; the third isostatically pressed block was sintered at a temperature of 1550°C for 15 hours to obtain a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3.

[0037] The obtained (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 ) The electrical performance of CrO3 negative temperature coefficient thermistor ceramic material was tested, and the electrical parameters obtained were B 0℃ / 1300℃ =2044 ±1.42% K,ρ 1300℃ =1.45×10 3 ±1.73% Ω·cm. At the same time, the prepared (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 ) The relationship between the resistance drift rate and aging time of CrO3 material at 1300 °C was measured. The test results are as follows Figure 3 shown.

[0038] The present invention is not limited to the above-mentioned specific embodiments, but extends to any new features or any new combination disclosed in this specification, as well as any new method or process steps or any new combination disclosed.

Claims

1. A high entropy rare earth chromate high temperature negative temperature coefficient thermistor material, characterized in that: Its chemical formula is (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3; The electrical performance parameters of the negative temperature coefficient thermistor material are as follows: 0℃ / 1300℃ = 2044 ±1.42% K, ρ 1300℃ =1.45×10 3 ±1.73% Ω·cm, applicable temperature range is 0℃-1300℃; The negative temperature coefficient thermistor material is prepared by a method comprising the following steps: a. According to the molar ratio of La:Nd:Sm:Eu:Gd:Cr=1:1:1:1:1:5, weigh oxide powders of lanthanum trioxide, neodymium trioxide, samarium trioxide, europium trioxide, gadolinium trioxide and chromium trioxide respectively and mix them to obtain an initial mixture; after wet three-dimensional vibration ball milling the initial mixture for 8-12 hours, dry the wet-milled slurry at a temperature of 100°C, take it out and place it in an agate mortar for manual grinding for 1-4 hours to obtain a precursor powder; b. calcining the precursor powder obtained in step a at 1100° C. for 2 to 6 hours, and then manually grinding for 0.5 to 10 hours to obtain a perovskite phase powder; c. Pressing the perovskite phase powder obtained in step b into blocks using a uniaxial hydraulic press to obtain a second formed block; The second formed block is subjected to cold isostatic pressing to obtain a third isostatic pressing block; the third isostatic pressing block is sintered at 1550° C. for 5-35 hours to obtain a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material.

2. The high entropy rare earth chromate high temperature negative temperature coefficient thermistor material according to claim 1, characterized in that: In the step a, oxide powders of lanthanum trioxide, neodymium trioxide, samarium trioxide, europium trioxide, gadolinium trioxide and chromium trioxide are weighed and mixed according to the molar ratio of La:Nd:Sm:Eu:Gd:Cr=1:1:1:1:1:5, placed in a ball mill, agate is used as the ball milling medium, and analytical pure anhydrous ethanol is used as the dispersion medium, and wet three-dimensional vibration ball milling is performed for 8 hours. The wet-milled slurry is dried at a temperature of 100°C, taken out, placed in an agate mortar and manually ground for 2 hours to obtain a precursor powder.

3. The high entropy rare earth chromate high temperature negative temperature coefficient thermistor material according to claim 1, characterized in that: In step b, the precursor powder obtained in step a is calcined at 1100° C. for 5 hours and then manually ground for 2 hours to obtain a perovskite phase (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3 powder.

4. The high entropy rare earth chromate high temperature negative temperature coefficient thermistor material according to claim 1, characterized in that: In the step c, the third isostatically pressed block is sintered at 1550° C. for 15 hours to obtain a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material.

5. The high entropy rare earth chromate high temperature negative temperature coefficient thermistor material according to claim 4, characterized in that: In the step c, the perovskite phase powder obtained in step b is pressed by a uniaxial hydraulic press at 15 kg / cm 2 The second molded block was pressed at a pressure of 300 MPa for 2 minutes to obtain a second molded block; the second molded block was cold isostatically pressed and maintained at a pressure of 300 MPa for 3 minutes to obtain a third isostatically pressed block; the third isostatically pressed block was sintered at a temperature of 1550°C for 15 hours to obtain a high-entropy rare earth chromate high-temperature negative temperature coefficient thermistor material (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3.

6. Application of the high entropy rare earth chromate high temperature negative temperature coefficient thermistor material according to any one of claims 1 to 5 in the field of semiconductor sensors, wherein the chemical formula of the high entropy rare earth chromate high temperature negative temperature coefficient thermistor material is (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 G 0.2 )CrO3.

Citation Information

Patent Citations

  • Chromic acid rare earth high-entropy ceramic powder for low-frequency sound absorption and composite material and application thereof

    CN114591077A

  • Oxygen-insensitive negative temperature coefficient heat-sensitive material based on high-entropy rare earth zirconate

    CN115894029A